An In Vivo Assessment of the Effect of Hexane Extract from Endlicheria paniculata Branches and Its Main Compound, Methyldehydrodieugenol B, on Murine Sponge-Induced Inflammation - Bruno Antonio Ferreira; Rafael Aparecido Carvalho Souza; Francyelle Borges Rosa de Moura; Tiara da Costa Silva; Tais da Silva Adriano; Eduardo de Faria Franca; Raquel Maria Ferreira de Sousa; Fernanda de Assis Araújo; João Henrique Ghilardi Lago; Alberto de Oliveira (Molecules, 2023)
The present study aims to explore the anti-inflammatory potential activity of the hexane extract from branches (HEB) of Endlicheria paniculata (Lauraceae) and its main compound, methyldehydrodieugenol B, in the inflammatory response induced by a murine implant sponge model. HPLC-ESI/MS analysis of HEB led to the identification of six chemically related neolignans, with methyldehydrodieugenol B as the main compound. An in silico analysis of the pharmacokinetic parameters of the identified compounds suggested moderate solubility but good absorption and biodistribution in vivo. Thus, the treatment of mice with HEB using in vivo assays indicated that HEB promoted pro-inflammatory, antiangiogenic, and antifibrogenic effects, whereas treatment with methyldehydrodieugenol B caused anti-inflammatory, antifibrogenic, and antiangiogenic effects. The obtained results shown the therapeutic potential of HEB and methyldehydrodieugenol B in the treatment of pathologies associated with inflammation and angiogenesis, including chronic wounds.